أصـول الفـقه عند الحـنفـية وأهم مميزاته فـي القرن الثامـن الهجري - Hatib, Raid (Fatih Sultan Mehmet Vakıf Üniversitesi, 2024)
İslâm fıkhını, geçirdiği evreleri, fıkhın müslümanların kalbindeki yerini ve özellikle de gökten inen şer'î hükümler ile mükellef olan insanların fiilleri arasındaki irtibatı doğru bir şekilde inceleyen kişi bu şeriatın üstünlüğünü açıkça görecektir. Âlimlerimizin İslâm fıkhını son derece güzel bir şiirin mısraları gibi bize sunduğunu, o hükümlerin en usta bir ressâm eliyle çizilmiş bir tablo gibi durduğunu anlayacaktır. İşte bu durum; kültür mirâsımızın büyüklüğünü göstermekte, bizim için bu önsözü ve peygamberliğin hidayet nurundan beslenenen bu mükemmel yöntemi dokuyanların kıymetini hissettirmektedir. Bu yöntem, bize gelen şer'î nasların okunup incelenerek özünün ve mükelleflerin fiillerine uygulanacak fıkhî hükümlerinin çıkarılması usûlüne dayanıyordu. Alimlerimiz bu naslardan, fer'î ve özel hükümlerin türetilmesine temel teşkil eden küllî ve genel kâideleri çıkarmaya gayret ettiler. Genel hükümleri içeren genel kâideleri tayin ettikten sonra özel ve ayrıntılı hükümleri çıkarabilmek için tafsîlî naslara yönelip amel etsinler diye mükelleflerin önüne serdiler. Naslarda açıkça geçmeyen yeni olayları ise belirlenen kıyas kurallarına uygun bir şekilde naslarda bulunan benzerlerine kıyas ettiler. Bizim kültürümüzde "Fıkıh" ve "Usûl-u Fıkıh" denilen ilimler bu şekilde ortaya çıkmış oldu. Daha sonra kolaylık için bu çok sayıdaki hükmü toplayıcı belli kâideler koydular. Bundan dolayı "Kavâid-i Fıkhiyye" ve "Zavâbıt-ı Fıkhiyye" ilimleri meydana geldi. İnsanlar bu ilimlerle ilgilendikçe, geçmişlerini takip eden ve kapalı yerleri açan alimlerimizin elinde bu ilimlerin terimleri farklı evrelerden geçerek genişlemeye başladı. Böylece fıkıh ve usûl-u fıkıh, bize bu kültürü aktaran çeşitli faydalar ile yenilenmiş ve taze halde ulaşmış oldu. Bu tezde ise alimlerin bu fennin terminolojisini çok titiz bir şekilde düzenledikleri ve bu fennin neredeyse altın çağlardan biri olan dönemde meydana gelen gelişmelere ışık tutmak için sadece sekizinci asırda hanefî alimlerinin usûlunü anlatmakla yetindim. Çalışmam giriş, dört fasıl ve sonuçtan oluşmaktadır. Giriş bölümünde usûl-u fıkhın mânâsından, hanefîler nezdindeki tarihî gelişmelerden ve bu dönemler içerisinde yazılmış önemli kitaplardan bahsettim. Birinci fasılda sekizinci asrın siyasî durumundan ve ilmî hareketliliğinden bahsettim. Çünkü bu asırdaki siyasî durumun âlimler, dolayısıyla ilmî çalışmalar ve özellikle de tedvîn faaliyetleri üzerinde büyük etkisi bulunuyordu. Tıpkı "Zor zamanlar büyük eserler doğurur." sözünde olduğu gibi. İkinci fasılda sekizinci asırda hanefî mezhebi ekolünü, en önemli âlimlerini ve o dönemde yazılmış eserleri anlattım. Üçüncü fasılda hanefî ekolünü ve ayırt edici en önemli özelliklere ışık tuttum. Dördüncü fasılda ise o asırda yazılan en mühim kitapların ayrıntılı incelemesine yer verdim. Sonuç kısmında da çalışmam boyunca ulaştığım önemli neticeleri, belli tavsiyeleri ve konu fihristini eklemiş oldum. Allâh celle celâluhû doğruya ulaştırandır.

Anyone who follows Islamic jurisprudence, its developments, and its lofty position in the hearts of the Islamic community, because of the clarification of the link between the legislation that came down from heaven and the action of the accountable person to whom the speech was directed, will find the greatness of this legislation How Our scholars have created a beautiful system for us, as if it were a painting carefully created by the most skilled painters. This makes us feel the greatness of our heritage and the greatness of those who wove that preamble for us, as well as that integrated approach derived from the source and guidance of prophecy. This technique was based on a strategy that involved reading and evaluating the contained legal provisions to extract their content and the jurisprudential rules to be applied to the acts of those in charge.Our scholars made an effort to derive from those writings the general norms that served as the foundation for establishing sub-partial verdicts. So the scholars decided on the overall norms, which included the general rulings, and then went to the detailed texts to extract the detailed partial rulings, which they placed in the hands of the accountable person to act on, as stated in them.They utilized to compare new rulings and tragedies that were not included in the book to their counterparts that were.The book adheres to the measurement guidelines established by our scholars. Thus, what is known as the science of principles and the science of jurisprudence emerged among us, and they built rules and regulations for these numerous verdicts in order to facilitate their control.So what is known as the science of jurisprudential rules and controls evolved, and these disciplines began to appear to people, with their terminology and rules developing and expanding throughout time at the hands of our academics who continued to follow those who came before.With the understanding of what they missed, jurisprudence and its principles developed for us in our time, honed and refined, and full of benefits, uniqueness, and jokes that influenced us this magnificent legacy. Our thesis focused solely on describing the ideas of jurisprudence among our Hanafi thinkers in the eighth century.To shed light on the advances that occurred throughout this time period, our experts meticulously refined the language of this art till it was nearly one of its golden eras. My essay consisted of an introduction, four chapters, and a conclusion.In the beginning, I mentioned the significance of the principles of jurisprudence, and a historical review of the fundamental advancements of the Hanafi masters, including the most important books written throughout these ages. Then, in the first chapter, I mentioned the political situation and scientific freedom that the eighth era experienced > because the political situation had a great impact on the souls of scholars and thus on the scientific movement, especially in the codification process, as it is said that creativity is born from the womb of adversity.Then, in the second chapter, I introduced the eighth-century Hanafi School.The third chapter provides insight into the Hanafi school's approach in this age, focusing on its key scholars and writings. Its most notable qualities were those that characterized it.The fourth chapter discussed a careful assessment of the most prominent fundamentalist texts written during this era. Then, in the conclusion, I explained the indexes and the most relevant results and recommendations that emerged to me during my research. May Allah grant success to the right path
Hicrî 8. yüzyılda Hanefî fıkıh usulü ve en önemli özellikleri
Keywords: Din; Religion